Evaluation of exaggerated claims in the abstracts of systematic reviews reporting accelerated orthodontic tooth movement: a meta research analysis - Shyagali Tarulatha R.; Rathore Ayesha; Kapoor Shanya; Gupta Abhishek; Tiwari Anil; Patidar Rahul (Sciendo, 2022)
The latest trend in scientific literature review is to scrutinise the practices of false or biased reporting of findings, which is rightly termed as 'spin'. In recent years, accelerated tooth movement has gained attention from the orthodontic community, but the findings still remain unclear and controversial.